Neck and Shoulder Pain with Scapular Dyskinesis in Computer Office Workers - Seong Eun Moon; Young Kyun Kim (Medicina, 2023)
Background and Objectives: Computer office workers spend long periods in front of a computer, and neck and shoulder pain are common. Scapular dyskinesis (SD) is associated with neck and shoulder pain. However, SD in computer office workers has not been elucidated. We aimed to investigate the prevalence of SD, neck and shoulder pain, disability, and working hours in computer office workers. Materials and Methods: In total, 109 computer office workers participated in this study. The results of a scapular dyskinesis test (SDT), lateral scapular slide test (LSST), neck disability index (NDI), shoulder pain and disability index (SPADI), visual analog scale (VAS) scores of the neck and shoulder, and working hours were recorded. Results: Ninety-eight computer office workers (89.9%) had SD. Computer office workers with SD had significantly higher NDI (p = 0.019), neck VAS (p = 0.041), and dominant shoulder VAS scores (p = 0.043). The LSST results showed a significantly greater distance (p = 0.016) in participants with SD. Conclusions: The prevalence of SD was very high in computer office workers, and neck and shoulder pain were more prevalent in workers with obvious SD.